Endotoxin contamination in ovalbumin as viewed from a nano‐immunotherapy perspective. (10th August 2021) - Pang, Guibin; Liu, Yun; Wang, Yangyun; Wang, Yong; Wang, Fujun; Zhao, Jian; Zhang, Leshuai W.
Abstract: Ovalbumin (OVA) is a model antigen commonly incorporated in smartly designed nanoparticles for delivery into antigen‐presenting cells (APC), aiming to investigate the immune activity and therapeutic efficacy of nanoparticles that contain immunoregulatory compounds. However, the immunoresponse observed in nano‐immunotherapy may unexpectedly arise from endotoxin impurity of OVA in the nanoparticles. Literature review shows that most researchers did not notice the importance of endotoxin‐free OVA when used in nano‐immunotherapy studies. Concentration at as low as 5 μg/ml OVA from Sigma‐Aldrich (contains 0.625 ng/ml endotoxin) was able to activate APC such as dendritic cells and macrophages. Here, we proposed that the endotoxin impurity in OVA or the finished nanoproducts should be determined by both Limulus Amebocyte Lysate (LAL) and cell‐based assay, to ensure the endotoxin‐free quality of the nanoparticles. The endotoxin in OVA can be removed by endotoxin removal column and phase separation methods and endotoxin‐free OVA can be purchased. This perspective alerts the researchers of endotoxin impurity of OVA that may transfer into the finished nanoparticles and introduce an unfavorable immunoregulatory function with false‐positive results. OVA with minimal endotoxin level should be used in nano‐immunotherapy studies to accurately reflect the true effects of nanoparticles on the immune system. This article is categorized under: Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Abstract : Deceptive immunostimulation may be induced by endotoxin contamination of OVA protein in finished nanoparticles during tumor immunotherapy